Successful Pregnancy Outcome in end-stage Renal Disease (ESRD) Patient : A Case Report - Rashid, Maliha; Khan, MD Abdul Wahab; Hossain, Parisa Salsabil; Bushra, Umysa Taher; Akhter, Nusur (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Pregnancy in women with chronic kidney disease (CKD) has always been considered as a challenging event both for the mother and the fetus . Outcomes of pregnancy in patients with End stage renal disease ( ESRD ) have long been considered to be extremely poor and challenges are harder in ESRD patients undergoing maintenance hemodialysis( MHD) . The cases of successful full term pregnancy occurring in an ESRD patient are still very few in whole world even after the evolutionary improvement of medical care. Development of well established multidisciplinary center make it possible to bring a successful pregnancy outcome among ESRD patients who are on going MHD. Patients with CKD are usually amenorrheic and fertility is markedly reduced . Women with chronic kidney disease, who get pregnant have poor pregnancy outcome in term of fetus and mother. Here we report a case of 34 years old lady, mother of two children , housewife presented in Bangladesh Specialized Hospital with a diagnosis 3 rd G 29 weeks of pregnancy with ESRD (on maintenance hemodialysis) with Hypertension. She was treated conservatively with joint consultation with Consultant Obstetrician, Nephrologist and Pediatrician. Her elective Lower uterine segment Cesarean section (LUCS) was done at her 35 weeks of pregnancy due to fetal distress with previous history of 2 LUCS. Both the mother and baby were healthy while discharge from hospital. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 162-164